Proceedings of the 1st International Conference on Education Social Sciences and Humanities (ICESSHum 2019) 2019
DOI: 10.2991/icesshum-19.2019.51
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Flipped Classroom Strategy on Listening Comprehension of Undergraduate Students at English Department in IAIN Batusangkar

Abstract: This paper describes the effect of flipped classroom strategy toward students' listening comprehension in IAIN Batusangkar. The design of this study was quasi experimental in which there are two classes that become experimental class and control class.The population of the research was the first semester students of English Department in IAIN Batusangkar. The data were collect from listening comprehension test, based on homogeneity and normality testing. It was found that the data is homogenous and normal. T-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
1
2
0
2
Order By: Relevance
“…With regard to the first research question, examining whether flipped classroom approach contributes to the students' listening comprehension, especially for TOEFL listening session, the result revealed that the average scores of the post-test (Mean = 72.27) was higher than the average scores of pretest (Mean = 64.06), emphasizing that students performed considerably better on the post-test after having flipped classroom. Related to the evidence on the improvement of students' listening competence, the result of the present study is compatible with a plethora of previous studies (Ahmad, 2016;Alhamami & Khan, 2019;Astri et al, 2019;Khonamri et al, 2020;Roth & Suppasetseree, 2016;Wang, 2017). Yet, this study is slightly different from those previous studies since the listening competence focused on specific listening proficiency, TOEFL listening section.…”
Section: The Impact Of the Flipped Classroom On Efl Students' Listeni...supporting
confidence: 92%
“…With regard to the first research question, examining whether flipped classroom approach contributes to the students' listening comprehension, especially for TOEFL listening session, the result revealed that the average scores of the post-test (Mean = 72.27) was higher than the average scores of pretest (Mean = 64.06), emphasizing that students performed considerably better on the post-test after having flipped classroom. Related to the evidence on the improvement of students' listening competence, the result of the present study is compatible with a plethora of previous studies (Ahmad, 2016;Alhamami & Khan, 2019;Astri et al, 2019;Khonamri et al, 2020;Roth & Suppasetseree, 2016;Wang, 2017). Yet, this study is slightly different from those previous studies since the listening competence focused on specific listening proficiency, TOEFL listening section.…”
Section: The Impact Of the Flipped Classroom On Efl Students' Listeni...supporting
confidence: 92%
“…Yabancı dil öğreniminde dinleme, öğrencilerin hedef dildeki sözlü metni anlayabilmeleri, kelimeleri nasıl telaffuz edeceklerini öğrenebildikleri, kelimelerin tonlama ve vurgularını kullanabildikleri ve kelime dağarcıklarını geliştirdikleri becerileri kapsamaktadır (Astri, 2019)…”
Section: Yabancı Dil Eğitimiunclassified
“…Researchers have shown that flipped classroom has numerous benefits and in language learning [5], [6]. Nevertheless, students in the flipped classrooms should take their own learning responsibilities, in outof-class sessions prior to the in-class sessions.…”
Section: Introductionmentioning
confidence: 99%